Validation of the BetaStar® Advanced for Beta-lactams Test Kit for the Screening of Bulk Tank and Tanker Truck Milks for the Presence of Beta-lactam Drug Residues. (23rd November 2019) - Denhartigh, Andrew; Reynolds, Lindsay; Palmer, Katherine; Klein, Frank; Rice, Jennifer; Rejman, John J; Boison, Joe; Kijak, Philip; Shelver, Weilin
Abstract: A validation study was conducted for an immunochromatographic method (BetaStar ® Advanced for Beta-lactams) for the detection of beta-lactam residues in raw, commingled bovine milk. The assay detected amoxicillin, ampicillin, cloxacillin, penicillin, cephapirin, and ceftiofur below the U.S. Food and Drug Administration tolerance levels but above the maximum sensitivity thresholds established by the National Conference on Interstate Milk Shipments. The results of internal and independent laboratory dose-response studies employing spiked samples were in agreement. The test detected all six drugs at the approximate 90/95% sensitivity levels in milk from cows treated with each drug. Selectivity of the assay was 100%, as no false-positive results were obtained in testing 1148 control milk samples. Testing the estimated 90/95% sensitivity level for amoxicillin (8.5 ppb), ampicillin (6.9 ppb), cloxacillin (8.9 ppb), penicillin (4.2 ppb), and cephapirin (17.6 ppb), and at 100 ppb for each antibiotic, resulted in 94–100% positive tests for each of the beta-lactam drugs. The results of ruggedness experiments established the operating parameter tolerances for the assay. Cross-reactivity testing established that the assay detects other certain beta-lactam drugs, but it does not cross-react with any of 30 drugs belonging to seven different drug classes. Abnormally high bacterial or somatic cell counts in raw milk produced no assay interference.